THE EFFECT OF JOB SATISFACTION, PROCEDURAL FAIRNESS AND WORK MOTIVATION ON TEACHER PERFORMANCE IN SMA YUPPENTEK 1 TANGERANG MUNICIPALITY - Moh Abror (Dinasti Publisher, 2020)
This study aims to prove the influence of job satisfaction, procedural fairness and work motivation on teacher performance at Yuppentek 1 High School in Tangerang Municipality. By using 100% of a sample of 71 teachers, the main instrument was in the form of a questionnaire. Data in this study were analysed using (1) descriptive analysis of respondent characteristics (2) descriptive analysis of research variables and (3) analysis of Partial Least Square (PLS)-Structural Equation Modelling (SEM) with smartly 3.0. The results indicated that based on the results of data testing, the evaluation of the measurement model was valid and reliable and could be received substantially. Partial Least Square application test results showed that 73.3% of teacher performance variance is influenced by teacher job satisfaction. While 56.9% of the variance in teacher performance is influenced by procedural fairness in schools and 53.1% of the variance in teacher performance is influenced by teacher work motivation. Interpretation of the results of R Square and R Square Adjusted resulted that 48.6% of teacher performance is influenced by job satisfaction, procedural justices and teacher work motivation. However, 51.4% of teacher performance variance is influenced by other factors out of job satisfaction, procedural justice and teacher work motivation